How animals care for their babies - Hirschland, Roger B. (Washington, D.C. : National Geographic Society, 1987)
1. Parental behavor in animals--Juvenile literature .
Bibliography: p. [34].
Basic ed. students
Keywords: Parental behavior in animals -- Juvenile literature; Animals -- Infancy -- Juvenile literature; Parental behavior in animals; Animals -- Infancy